Growth Response in Oryctolagus cuniculus to Selenium Toxicity Exposure Ameliorated with Vitamin E. (9th May 2022) - Rehman, Rukhshanda; Sial, Nuzhat; Ismail, Amina; Hussain, Shabir; Abid, Sobia; Javed, Maryium; Nadeem, Khansa; Ayoub, Muhammad
Abstract : The adverse impacts of high temperature during the summer season on the rabbit industry have gained increased global attention. In this study, the comparative effects of biological (BIO) and chemical (CH) nanoselenium (nano-Se) combined with vitamin E on the growth and immune performances of rabbits were observed. A total of 200 white male rabbits of similar age (90 days) were divided into five treatment groups (T0, T1, T2, T3, and T4), 40 animals in each treatment. The rabbits in the first treatment group (T0) was fed basal diet; (T1) basal diet supplemented with 35 mg biological synthesized nanoselenium/kg diet; (T2) basal diet with 35 mg biological nanoselenium/kg diet+150 mg Vit. E/kg; (T3) basal diet+35 m chemically synthesized nanoselenium/kg diet; and (T4) basal diet+35 mg of chemical nanoselenium/kg diet+150 mg Vit. E/kg. The duration of this experiment was 63 days. The body weight of each rabbit was recorded weekly. Results revealed a significant (P < 0.05 ) increase in live body weight (LBW), total body gain (TBG), and feed conversion ratio (FCR) of rabbits treated with BIO-Se+Vit. E (T2) compared to the other groups. Selenium concentrations in the kidneys and liver were significantly higher (P < 0.05 ) in animals fed with BIO-Se+Vit. E (T2). The concentrations of serum urea, glutamyl transferase (GGT), and triglycerides (TG) were lower in untreated (T0) and treated groups (T1, T2, T3, and T4). From the results of this study, it can be concluded that biological nano-Se gave maximum improvement for the parameters under study compared to the chemically synthesized nanoselenium by playing a role in alleviating heat stress, increasing the growth performance, and enhancing the immunity of growing white male rabbits. Further addition of Vit. E is an alternative method to maximize productivity with no adverse effects during the fattening period of growing white male rabbits.